Plastics and sustainable purchase decisions in a circular economy: The case of Dutch food industry (2020)
Every day, society’s concern over pollution caused by plastic waste grows greater. One of the most intensive sectors for the use of plastic is the food industry. Companies in this sector face the challenge of transitioning to a more sustainable and less intensive model of plastic use, respecting the principles established for a circular economy. Accordingly, one of the questions that industries tend to ask is whether sustainability will influence the consumer’s purchase decision. To respond to this, the factors that determine a consumer’s sustainable purchase decision in relation to the plastic and food industry have been analyzed in this paper. For this, a regression analysis was performed on a sample of Dutch consumers. The results show that the decision of purchase of the consumer of the Food Industry is conditioned by factors such as age, sustainable behavior, knowledge of the Circular economy and the perception of usefulness of plastic.